Knowledge on Voluntary Medical Male Circumcision in a Low uptake Setting in Northern Uganda - Nanteza, Barbara Marjorie; Serwadda, David; Kankaka, Edward Nelson; Mongo, Grace Bua; Gray, Ronald; Makumbi, Frederick Edward (BMC public health, 2018)
Free VMMC services have been available in Uganda since 2010. However, uptake in Northern Uganda remains disproportionately low. We aimed to determine if this is due to men’s insufficient knowledge on VMMC, and if women’s knowledge on VMMC has any association with VMMC status of their male sexual partners.
Keywords: Sexual function; VMMC; Knowledge; Circumcision; Misconception